Unmasking MRSA antibiotic resistance: the impact of environment, pollution, and healthcare quality—a nationwide exploration in China: a comprehensive analysis spanning 2014 to 2021 in mainland China - Yi-Chang Zhao; Ming-Xuan Xiao; Zhi-Hua Sun; Jia-Kai Li; Huai-yuan Liu; Bi-Kui Zhang; Hua-Lin Cai; Wei Cao; Feng Yu; Miao Yan (Environmental Sciences Europe)
Abstract Background The rise of antibiotic resistance has become a critical global health concern, resulting in numerous fatalities annually. Among resistant pathogens, methicillin-resistant Staphylococcus aureus (MRSA) poses a particularly severe and expanding threat. However, there is a lack of comprehensive studies on the prevalence, patterns, and contributing factors of MRSA resistance within mainland China. Methods In this study, the data of MRSA antimicrobial resistance in 31 provinces from 2014 to 2021 were obtained from the China Antimicrobial Resistance Surveillance System (CARSS). Environment and medical care data were obtained either from the National Bureau of Statistics (NBS) database or the National Ministry of Ecology and Environment (NMEE). Multiple linear regression and restricted cubic spline (RCS) was used to explore the potential influencing factors of MRSA antibiotic resistance rate (AMR). Results Significant positive associations were identified between MRSA AMR and various factors, including cadmium pollution, soybean and poultry production, and oil consumption. Conversely, an inverse J-shaped relationship was observed between tap water coverage and MRSA resistance. Other noteworthy correlations included the effects of corn and pork production, as well as antibiotic use intensity. Our predictive model explained 52.7% of the variability in MRSA AMR, demonstrating strong predictive capability. Conclusions This study highlights the significant role of environmental, agricultural, and healthcare factors in influencing MRSA AMR in China. The findings emphasize the need for integrated strategies addressing regional environmental and healthcare quality in combating antibiotic resistance. Extending this research globally could enhance understanding of MRSA resistance dynamics on a broader scale. Graphical Abstract